2010
DOI: 10.1017/s0263034609990668
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced optical breakdown applied for laser spark ignition

Abstract: In the present article, the experimental investigation of optical breakdown induced by ns/mJ pulses at two wavelengths, 1064 nm and 532 nm, in air of atmospheric pressure is reported and discussed. The obtained breakdown thresholds were compared with theory and are in good agreement. The generated plasmas have been characterized by their amount of scattered laser light, energy transmission, and change of the transmitted temporal shape. Laser-induced plasma formation in a gas, in air, also generates an acoustic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The same is clear from the shadowgraphs ( Fig. 3a-3f) corroborating with higher deposition of laser energy before the geometrical focus of the focusing optics (Monot et al, 1992;Schwarz et al, 2010) and with the observed on-axis self-emission intensity profiles (Fig. 3i).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…The same is clear from the shadowgraphs ( Fig. 3a-3f) corroborating with higher deposition of laser energy before the geometrical focus of the focusing optics (Monot et al, 1992;Schwarz et al, 2010) and with the observed on-axis self-emission intensity profiles (Fig. 3i).…”
Section: Resultssupporting
confidence: 81%
“…Laser-plasma induced shockwaves in air threshold the low dense plasma created around the focal plane interacts with the laser pulse leading to deposition of energy at different positions along the propagation direction analogous to self-focusing, a phenomenon well-known for high-power laser beams propagating in air (Shen, 1984;Monot et al, 1992;Schwarz et al, 2010). Figure 4 shows R SW as a function of delay from the laser pulse for 50, 75, and 150 mJ laser energies.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, in the case of APPJ processing, the nozzle can be corroded by the plasma, requiring regular maintenance. Besides plasma ignition by electrical energy like RF or microwave power, plasma can also be generated in gas by laser radiation due to optical break down [14][15][16]. An optical breakdown can be achieved by focusing a laser beam in a gas when a critical power density is exceeded.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies concerning the energy transfer and the plasma breakdown have been carried out with actively Q-switched nanosecond Nd:YAG lasers at fundamental or frequency-doubled wavelength. Schwarz et al [9] show that 532 nm radiation is advantageous for generating a plasma breakdown because of tighter focus area, whereas 1064 nm radiation is advantageous for transferring more energy to the plasma due to a greater plasma absorption efficiency. Moreover, investigations show that increasing focal length leads to raised minimum energy for ignition (MIE) and lower power density [10,11].…”
Section: Introductionmentioning
confidence: 99%